1994
DOI: 10.1111/j.1432-1033.1994.tb20017.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Enkephalin and Dermorphin into δ‐Selective Opioid Antagonists by Single‐Residue Substitution

Abstract: The properties of di-and tri-peptides containing 1,2,3,6tetrahydroisoquinoline-3-carboxylic acid (Tic) in second position suggest that the message domain of opioid peptides can be composed of only two residues [Temussi, P. A., Salvadori, S., Amodeo, P., Guerrini, R., Tomatis, R., Lazarus, L. H., Picone, D. & Tancredi, T. (1994) Biochem. Biophys. Res. Commun. 198,. As a crucial test of the possibility that the Tyr-Tic segment be a message domain in longer peptide sequences, we have inserted it in the sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…In spite of the different configuration of the peptide bond, both conformers (i.e. c/T/T and t/T/T) have a similar compact shape reminiscent of that of the conformer of Tyr-Tic-NH 2 (Clb + f) that we proposed as the bioactive conformation of that antagonist [2,4].…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In spite of the different configuration of the peptide bond, both conformers (i.e. c/T/T and t/T/T) have a similar compact shape reminiscent of that of the conformer of Tyr-Tic-NH 2 (Clb + f) that we proposed as the bioactive conformation of that antagonist [2,4].…”
Section: Resultsmentioning
confidence: 79%
“…Notwithstanding, to make a homogeneous comparison with the solution study of Tyr-Tic-NH> we ran all quantitative experiments in a 90110 (v:v) DMSOa6/H20 cryoprotective mixture [2] at 278 K. In fact, we have shown that the use of biocompatible media with viscosities of the order of 7 10 cp, not only leads to a quantitative increase of all NOEs observed at lower viscosity, as expected by the theory of microviscosity, but also to selective growth of (conformationally diagnostic) effects involving backbone protons with respect to intrachain ones [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before drawing any conclusion it is (essential to investigate the conformational preferences of this molecule, also in view of the observation that the corresponding linear compound [Ac-Tyr(Me),-Tic-NH,] shows a higher antagonism but a lower binding affinity. The increase of antagonistic potency of cycle[-Tyr(Me),-Tic-] with respect to cyclo(-Tyr-Tic-) can be attributed to different conformational preferences and/or greater affinity of the Tyr(Me), side chain for the receptor, Since the apparent cause of the low activity of cyclo( -Tyr-Tic-) is the unfavorable 'sandwiched' arrangement of its aromatic rings [20], it is crucial to know whether cycle[-Tyr(Me),-Tic-] can exist in conformations characterized by a 90" arrangement of those rings, consistent with the bioactive conformations of Tyr-Tic-NH,, Tyr(Me),-Tic-NH, and naltrindole [9,10,13,221.…”
Section: Molecular Mechanics and Molecular Dynamics (Md)mentioning
confidence: 99%
“…An opioid antagonist lacking the basic nitrogen (Boc-Tyr-Pro-Gly-PheLeu-Thr-OH) has been reported [19], but the extreme difficulty of finding the bioactive conformation in a flexible linear peptide makes this compound of modest usefulness and prompted us to design a rigid antagonist. The N-terminal Tyr-Tic sequence offers a very versatile basis for the synthesis of such a molecule since the conformational preferences of this dipeptide are limited and very well studied [9][10][11]. As a first approximation we thought that a simple way to get a molecule with the right conformation of the two aromatic moieties and lacking the basic nitrogen might be to prepare the diketopiperazine of Tyr-Tic.…”
mentioning
confidence: 99%